2020
DOI: 10.1159/000507190
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Apoplexy Leading to Cerebral Infarction: A Systematic Review

Abstract: Background: Cerebral infarction caused by pituitary apoplexy (PA) is rare. To characterize the clinical features of cerebral infarction caused by PA, we performed a systematic review. Summary: The clinical symptoms are mainly sudden headache, hemiplegia, visual impairment, disturbance of consciousness, and ophthalmalgia in patients with cerebral infarction caused by PA. Treatment for this type of infarction is different from treatment for general acute cerebral infarction. Compared to patients who underwent em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 45 publications
0
33
0
Order By: Relevance
“…The optimal timing of surgery was under debate [ 15 ]. Some articles were in favor of early decompression surgery, as it may counter visual impairment, ICA blood flow and brain edema [ [16] , [17] , [18] ]. Endoscopic transsphenoidal surgery and craniotomy were among surgery options.…”
Section: Clinical Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimal timing of surgery was under debate [ 15 ]. Some articles were in favor of early decompression surgery, as it may counter visual impairment, ICA blood flow and brain edema [ [16] , [17] , [18] ]. Endoscopic transsphenoidal surgery and craniotomy were among surgery options.…”
Section: Clinical Discussionmentioning
confidence: 99%
“…Endoscopic transsphenoidal surgery and craniotomy were among surgery options. Endoscopic transsphenoidal surgery patients had a lower mortality rate and improved better [ 17 ]. In our patient, the left ICA was compressed by the pituitary tumor causing cerebral infarction.…”
Section: Clinical Discussionmentioning
confidence: 99%
“…In a recent literature review of cerebral infarction associated with PA, the pathogenesis was reported as being due to direct intracranial vascular compression or vasospasm, either separately or together. 14 Mechanical compression was most commonly unilateral, but rarely bilateral. Vasospasm has been postulated as being due to vasoactive substances being released by the tumor itself or by the compressed hypothalamus, or due to subarachnoid hemorrhage (SAH) from the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Its aetiology is either haemorrhage or infarction within the adenoma. Patients can present with varying signs and symptoms, most commonly including headaches, nausea, diminished visual acuity, temporal visual field cut, ophthalmoparesis and impaired mental status [1][2][3][4][5]. Risk factors for PA includes bromocriptine withdrawl or initiation, head trauma, intracranial hypertension, hormone stimulation of the gland (for example during pregnancy), large tumor, cavernous sinus invasion and anticoagulation [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…The apoplectic tumor secrets vasoactive substance which then enters the subarachnoind space and causes vasospams. Some authors believe both mechanisms are responsible [2,3,6].…”
Section: Cerebral Ischaemia Due To Pamentioning
confidence: 99%